Examining the Division of Housework among Potato Farmers in Serang Village Karangreja District Purbalingga Regency - Riany Aulia Shabila; Siti Mazidatul Qonita (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
Karangreja Sub-District is a potato-producing area. One of the producing areas is in Serang Village. Potato production in the sub-district has fluctuated due to several factors, namely fertilizers, pesticides, land area, and labour. Fertilizers and pesticides do not affect potato production. Potato farmers in Serang Village collaborate with the company so that the amount and type of fertilizers and pesticides used are the same. The land area also does not affect potato production because the land used is always the same. Labour is a factor that needs to be investigated further. This study examines the distribution of housework among potato farmers in Serang Village, Karangreja Sub-District, Purbalingga Regency. The research focuses on three aspects: 1) the distribution of productive housework, 2) the distribution of reproductive housework, and 3) the distribution of social housework. A qualitative descriptive approach is used, and the sample consists of 35 potato farmers selected through simple random sampling. Data is collected through questionnaires, observations, and document analysis. The Moser approach and work time outlay are used for data analysis. The findings reveal that productive housework, such as land preparation, planting, and harvesting, is predominantly carried out by husbands. Reproductive housework, including cooking, cleaning, and childcare, is mainly performed by wives. Social housework varies between husbands and wives, such as participation in recitation activities and farmer group meetings. The study contributes to understanding potato farmers' division of labour and housework.